Fetal drug therapy. - Evans, M I (1993)
Fetal drug therapy encompasses several areas, including the prevention of external genital masculinization in 21-hydroxylase deficiency syndrome (congenital adrenal hyperplasia), biochemical amelioration of methylmalonic acidemia, and biotin-responsive multiple carboxylase deficiency. The correction of cardiac arrhythmias has become relatively commonplace, and a reduction in the risks of neural tube defects is now possible with the use of preconceptual and early conceptual folic acid. Similarly, fetal function can be altered by the induction of fetal lung maturity using a number of agents; corticosteroids are the most common fetal pharmaceutic agent, and a number of other agents have also been tried. The most common route of administering pharmaceutic agents is through the mother and the placenta, although the direct administration of certain agents is becoming more common.